The concept of peace and victory in the domestic and foreign policy of Ukraine - Hryhorii Perepelytsia (Przegląd Geopolityczny)
As a phenomenon of the 21st century, the Ukraine-Russia war challenges neoliberal ideas about the loss of meaning of hard power and undermines claims that phenomena such as war no longer belong to contemporary international relations. On the contrary, it confirms the credibility of the neo-realist geopolitical paradigm. The purpose of this article is to examine the concept of peace and victory, in the context of the ongoing war, in Ukraine's domestic and foreign policy practice. Therefore, the first part of the article is devoted to the conceptualization of war, peace and victory. The second part examines the importance of the concept of war as a foundation of Ukraine's domestic policy, which helps to understand the value of peace. The last part of the article presents an analysis of Ukraine's foreign policy, which presents predictive assessments of the advent of peace and its impact on regional and global security. The optimistic prediction is that Europe will still find the strength to avoid the mistakes of the past, overcome its fear of Russia and make efforts to maintain the old post-bipolar order. Outlining the contours of a new international security system is only possible if Russia is defeated. If this does not happen, the unipolar peace will be replaced by a multipolar peace, and the new security system of Eastern Europe will be based on a regional arrangement capable of repelling threats both from the East and from other directions. The leading role in it, after victory over Russia, will most likely belong to Ukraine.